Boris Pasternak doctor Zhivago - Pantheon (New York : Pantheon Books Inc., 1958)
Comprehensive picture of pre revolutionary upper-class Russian society and the revolutionary transition. Deals with the life of an intellectual and his heroic effort to preserve his capacity for reflection
Keywords: History; Russian Literature; Novel